A phytosterol-enriched saw palmetto supercritical CO2 extract ameliorates testosterone-induced benign prostatic hyperplasia by regulating the inflammatory and apoptotic proteins in a rat model - Heggar V. Sudeep; Karempudi Venkatakrishna; Ballal Amrutharaj; Anitha; Kodimule Shyamprasad (BMC, 2019)
Abstract Background Benign prostatic hyperplasia (BPH) is a pathological condition affecting older men. BPH complications often lead to deterioration in the quality of life. Serenoa repens (Saw Palmetto) is used for treating lower urinary tract infections in traditional medicine. Methods This study was performed to compare the efficacy of β-sitosterol enriched saw palmetto oil (VISPO) and conventional saw palmetto oil (SPO) extracted using supercritical fluid extraction, in alleviating the BPH complications using testosterone-induced BPH model rats. The animals received testosterone (5 mg/kg s.c.) with or without SPO and VISPO (200 and 400 mg/kg b.w.) or Finasteride (1 mg/kg b.w.) p.o. for 28 days. At the end of the experiment, overnight fasted animals were euthanized, blood samples collected for serum analysis of testosterone. Prostate tissue histomorphology was examined by hematoxylin and eosin (H&E) staining. Western blot analysis was performed using prostate tissue homogenates. Results VISPO exhibited superior efficacy compared to SPO as evident from the significant decrease in prostate weight to body weight ratio, serum testosterone level and increase in growth inhibition of prostate tissue compared to BPH group (p < 0.001). Histological examination of prostate tissue samples showed that VISPO treatment was comparatively better than SPO in improving the hyperplastic patterns. Further, VISPO significantly regulated the expression of inflammatory and apoptotic marker proteins in BPH rats. Conclusion Our data provide experimental evidence that β-sitosterol enriched saw palmetto oil could be higher efficacious in treating the BPH complications compared to the conventional saw palmetto oil preparations.